Application of photogrammetry and laser scanner on the Bronze Age structures of the Castillejos de Luna cist tomb necropolis (Pizarra, Spain) - Alejandro Muñoz-Muñoz; Diego Fernández-Sánchez; Eduardo Vijande-Vila; Serafín Becerra-Martín; Juan Jesús Cantillo-Duarte; Salvador Domínguez-Bella; Virgilio Martínez Enamorado; Francisca Rengel Castro; Pedro Cantalejo Duarte; María del Mar Espejo-Herrerías; José Suárez-Padilla; Juan Antonio Martín-Ruiz; et al. (Virtual Archaeology Review)
The cist tombs necropolis at Castillejos de Luna, in Sierra de Gibralmora-Sierra del Hacho (Pizarra, Málaga, Spain) was known from the graphic documentation and the grave goods of two tombs. New studies have documented nine burials. The aim of this article is to present the new virtualisation work that has been carried out in the necropolis, to generate a new three-dimensional (3D) documentation of the currently known records, which are in acceptable visibility conditions. Using tools to document tombs in 3D offers us great advances in data acquisition and editing, with great precision and realism, thanks to the 3D models generated through techniques such as photogrammetry or laser scanning. Thanks to these tools, it is possible to carry out studies on digital twins and use them as informative material for society. The study this paper describes has generated high quality products for dissemination and future analysis. The results shown here are of metric character, with orientation and geographical location of the structures. In addition, in one of the tombs the authors show the combination of photogrammetric techniques with laser scanners to obtain a single high-resolution 3D model; subsequently a retopology process is carried out to achieve a "light" model with a photorealistic appearance that is both easily manipulated on mobile devices for its dissemination and a guarantee that the general public can enjoy this necropolis in a different way. The preliminary results are published in the web repository of 3D models Sketchfab, where the users can see a preview of one of the tombs before and after being optimised with retopology through Blender. The authors provide a socio-historical analysis of Bronze Age necropolises in central Andalusia, within the framework of a debate on the western expansion of the El Argar Culture.